The "Stuff" of Class: How Property Rules in Preschool Reproduce Class Inequality. (20th July 2021) - Stockstill, Casey
Abstract: How does access to property shape children's experiences of institutions? Can access to property in preschool counter class inequality? Using two years of ethnographic data from a preschool serving middle-class, white children and a preschool serving poor children of color, I explore how access to and control over objects such as toys shapes children's school experiences. I found that preschools created different experiences of property: precarious property and protected property . Poor children of color experienced precarious property: personal objects were forbidden at school due to the risk of theft or loss. Teachers' loose supervision meant that children sometimes had classroom toys taken by peers. In contrast, middle-class, white children experienced protected property; teachers' rules encouraged children to bring some personal property, which was kept safe at school. Teachers' close supervision also allowed children to securely enjoy classroom toys. These property rules meant that white, middle-class preschoolers could assert individuality and control through property. Meanwhile, poor preschoolers of color had limited school-sponsored opportunities to assert individuality through personal property. I argue that property rules at preschool can reproduce class inequality.